GLENOID LABRAL CYST PRESENTING WITH SUPRASCAPULAR NERVE PALSY - Shetty, Siddharth M.; R., Rajsankar N.; Shetty, B. Jayaprakash (Journal of Health and Allied Sciences NU, 2014)
Introduction: Glenoid labral cyst in shoulder is an entity akin to meniscal cysts in knee. It usually manifests with features similar to impingement syndrome or rotator cuff weakness.Clinical Picture: A 42yr old male patient with complaints of left shoulder pain and restriction of movement for 2 months with muscle wasting in left supraspinatus and infraspinatus region. MRI left shoulder showed partial tear of supraspinatus tendon, glenoid labral cyst in closed proximity and causing compression to suprascapular nerve with atrophy of infraspinatus muscle.Treatment: Left shoulder diagnostic arthroscopy was done and followed with ganglion excision done through a posterior approach and suprascapular nerve was decompressed. Histopathology report showed features of an inflammatory cystic lesion.Outcome: patient experienced resolution of symptoms within 4 months of surgery with significant restoration of rotator function and bulk.Conclusion: Suprascapular nerve compressive neuropathy secondary to glenoid labral cyst is a rare entity but easily recognizable on a MRI scan and responds quickly to decompression.
Keywords: impingement; Suprascapular Nerve Compression